2007
DOI: 10.1080/01635580701328362
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid (DHA), a Primary Tumor Suppressive Omega-3 Fatty Acid, Inhibits Growth of Colorectal Cancer Independent of p53 Mutational Status

Abstract: Human colon carcinoma COLO 205, carrying wild type p53, grown subcutaneously in athymic mice was inhibited 80% by a high fat menhaden oil diet containing a mixture of omega-3 fatty acids compared to the low fat corn oil diet containing omega-6 fatty acids. Feeding a high fat diet of golden algae oil containing docosahexaenoic acid (DHA) as the sole long chain omega-3 fatty acid resulted in 93% growth inhibition. Similar findings were previously reported for WiDr colon carcinoma containing mutated p53 (His237).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 35 publications
4
48
0
2
Order By: Relevance
“…Studies with fish oil, which contains eicosapentaenoic acid and docosahexaenoic acid (DHA) showed that it has anti-inflammatory and anti-cancer properties. DHA treatment inhibits colon cancer growth through inducing apoptosis and cell-cycle arrest [68]. DHA also suppressed arachidonic acid-induced cell proliferation, PGE 2 production, and COX-2 expression in human colon carcinoma cells [69].…”
Section: Chemopreventive Mechanisms Of Carotenoidsmentioning
confidence: 98%
“…Studies with fish oil, which contains eicosapentaenoic acid and docosahexaenoic acid (DHA) showed that it has anti-inflammatory and anti-cancer properties. DHA treatment inhibits colon cancer growth through inducing apoptosis and cell-cycle arrest [68]. DHA also suppressed arachidonic acid-induced cell proliferation, PGE 2 production, and COX-2 expression in human colon carcinoma cells [69].…”
Section: Chemopreventive Mechanisms Of Carotenoidsmentioning
confidence: 98%
“…LCFA include palmitic acid (C16:0) (PMA), α-linolenic acid (18:3) (ω-3), conjugated linoleic acid (18:2) (ω-6) (CLA), linoleic acid (18:2) (ω-6) (LA), oleic acid (18:1) (ω-9) (OA), arachidonic acid (22:4) (ω-6) (AA), eicosapentaenoic acid (EPA) (20:5) (ω-3) and docosahexaenoic acid (DHA) (22:6) (ω-3). 38,[84][85][86] LCFA have demonstrated in-vitro anti-neoplastic properties in breast, prostate and CRC cell lines by cellular differentiation, cell cycle arrest and increasing oxidative stress, all leading to the induction of apoptosis. 30,87 Induction of apoptosis by LCFA in colorectal cancer cell lines.…”
Section: Long Chain Fatty Acids (Lcfa)mentioning
confidence: 99%
“…These investigators concluded that DHA exerted antitumorigenic activities dependent on p53 status, whereas EPA actions were p53 independent. 85 The related cell lines SW480 and SW620 demonstrated time-dependent cell cycle arrest when incubated with DHA, indicating that induction of cell death could be optimised through timing of administration of adjunctive therapy.…”
mentioning
confidence: 99%
“…LCFA have also demonstrated apoptotic properties, with palmitic acid, α-linoleic acid, CLA, and DHA inducing apoptosis in a range of CRC cell lines, including Caco-2, HTC-116, and COLO 205 cell lines. This is believed to be a consequence of lipid peroxidation, modification of cell cycle phases, induction of p21, an increase in the proapoptotic gene NAG-1, and altered P13 kinase and p38 MAPK pathways [13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%